If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x + -5)(2x) + -384 = 0 Reorder the terms: x(-5 + x)(2x) + -384 = 0 Remove parenthesis around (2x) x(-5 + x) * 2x + -384 = 0 Reorder the terms for easier multiplication: 2x * x(-5 + x) + -384 = 0 Multiply x * x 2x2(-5 + x) + -384 = 0 (-5 * 2x2 + x * 2x2) + -384 = 0 (-10x2 + 2x3) + -384 = 0 Reorder the terms: -384 + -10x2 + 2x3 = 0 Solving -384 + -10x2 + 2x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-192 + -5x2 + x3) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-192 + -5x2 + x3)' equal to zero and attempt to solve: Simplifying -192 + -5x2 + x3 = 0 Solving -192 + -5x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -6(7+8x)=294 | | 6w+15=-9w | | 4rx+ry=8sx+2sy | | 3x-20=50 | | t+(-14)=-1 | | 2wx-x=-5 | | 3(3y-2)+2y=16 | | -6-2(7z-2)=4(-6z+2)-4 | | 2-3f-5-5f=6 | | 2(0)-(9)= | | -8(1+7n)=-400 | | 3(8-z)-44=21z-4(5+6z) | | 2x-11=6x+9 | | 8.6+1.5x=17.7+x | | 26=4/u+2 | | 0.25x+4=0.12x+10 | | 9x^2+36=36x | | 3u+8=17 | | 2y+5/2-37/2=0 | | 6/p=5/11 | | 1-(3/(2x))=7/4 | | -6+5u=-16 | | 5+2n-2=7n+9-3n | | 3/p=7/9 | | -v+25=166 | | 36(2)= | | 114=155-v | | 3x+2x=-13 | | 166=-x+282 | | 0.06+0.03(100-x)=1.2 | | 7/3+4y=8y-1/15 | | 5[2x-7]=2 |